(untitled) (Journal of Engineering, 2003)
Contingency analysis is a valuable tool for a reliable planning and secure operation of a power system. Centingency analysis techniques must consider the impact of voltage effects as well as line flow effects. If the potential outage of a line or a generator would result in the overl rload of another line, then the system is said to be vulnerable. Without line overloading correction it may cause cascade outages and lead to failures in the whole system. An efficient contingency analysis model for detecting both branch MVA flow violations and bus voltage limit violations is presented. A fast technique has been developed for automatic contingency ranking and selection of contingency cases for a power system contingency analysis study A contingency list is built containing line and generator outages which are ranked according to their expected severity. System voltage performance index is used to assess events severity Another model that was used for line over-loading correction is based on a pseudo inverse method that was used to solve a non-square system of equations based on Lagrange’s theory in optimization These proposed models have been tested on the Iraqi National Grid system(case study) with 29 buses and 46 branches.